1986
DOI: 10.1093/nar/14.3.1159
|View full text |Cite
|
Sign up to set email alerts
|

Structure- and sequence-specificity of ozone degradation of supercoiled plasmid DNA1

Abstract: Ozone-reactive sites on the nucleobase moieties in supercoiled pBR322 DNA were investigated by using sequencing procedures. Ozonolysis in the absence of salt resulted in degradation of thymine residues in the A + T rich region located at 3100-3400bp. In the presence of salt, such as NaCl or MgCl2, a conformational change of plasmid DNA was induced. Subsequently the thymine and guanine residues in the loop of the cruciform located at 3120bp and 3220bp were degraded. In addition, central thymine residues present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
(17 reference statements)
1
12
0
2
Order By: Relevance
“…Hypersensitivity at specific A+T-rich sites is not a peculiarity of the mung bean nuclease since it is also found when other single-strand-specific nuclease probes [P1 nuclease, venom phosphodiesterase, and S1 nuclease (7,8,10,13)] are used under the same conditions. In addition, one and the same A+T-rich sequence in pBR322 is hypersensitive to a chemical probe (25) Fig. 2; 122 bp or -12 turns).…”
Section: Methodsmentioning
confidence: 99%
“…Hypersensitivity at specific A+T-rich sites is not a peculiarity of the mung bean nuclease since it is also found when other single-strand-specific nuclease probes [P1 nuclease, venom phosphodiesterase, and S1 nuclease (7,8,10,13)] are used under the same conditions. In addition, one and the same A+T-rich sequence in pBR322 is hypersensitive to a chemical probe (25) Fig. 2; 122 bp or -12 turns).…”
Section: Methodsmentioning
confidence: 99%
“…1981). Ozonolysis of supercoiled DNA has also been demonstrated (Sawadaishi et al . 1986), and both proteins and lipids are important targets in the reactions of ozone with bacterial membranes (Pryor and Uppu 1993).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, ozone in different forms has also been used in a large number of medical indications (Finch et al 1993;Alvarez et al 1997;Morris and Menendez 1997 2 ;Falcon Lincheta et al 1998;Komanapalli and Lau 1998 3 ). Ozone damages bacterial nucleic acids (Sawadaishi et al 1986). Structural analysis of tRNA has shown that degradation occurs preferentially at guanine residues (Shinriki et al 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Η αντιμικροβιακή δράση του όζοντος περιορίζεται στην υδατική φάση της επιφάνειας των τροφίμων, επειδή αποσυντίθεται γρήγορα πάνω στην τελευταία (Kim et al 1999). Το όζον καταστρέφει τα νουκλεϊκά οξέα των βακτηρίων (Sawadaishi et al 1986). Η δομική ανάλυσης του tRNA έχει δείξει ότι η υποβάθμιση συμβαίνει κατά προτίμηση στα υπολείμματα της γουανίνης (Shinriki et al 1981).…”
Section: μηχανισμος δρασης οζοντοςunclassified